Federalisme sebagai Alat Resolusi Konflik: Studi Kasus Bougainville, Papua Nugini - Hanafi, Muhammad Riza (Faculty of Social and Political Science, Universitas Siliwangi, 2023)
Bougainville is an autonomous region in Papua New Guinea which gained its autonomy through The Bougainville Peace Agreement (BPA). The conflict between the Bougainville Revolutionary Forces and the Papua New Guinean army was the worst in the South Pacific Region after World War II. The number of victims is estimated at 20,000 people. This conflict, which has been going on since before PNG became independent, was triggered by the mining issue which is intertwined with land ownership traditions. Civil war broke out in 1988 and ended in 1998 when both parties agreed to make peace. In 2001, Bougainville Peace Agreement was signed, and federalism became one of the